Foreign body reaction: towards a macrophage-centered adverse outcome pathway for fibrotic encapsulation - Meseberg, Tom; Kurz, Susanne; Spohn, Juliane (Frontiers in Toxicology, 2026)
The foreign body reaction (FBR), characterized by chronic inflammation and fibrotic capsule formation around implanted medical devices, remains a major cause in device-related complications. Current preclinical risk assessment relies on in vivo testing according to ISO 10993-6:2024, which are limited by species differences, incomplete mechanistic insight, and ethical concerns. Additionally, ISO/TS 10993-20:2006 outlines immunotoxicity knowledge regarding implant-induced effects such as FBR and specifies a collection of in vitro assays. The perspective presented here, aims to explore the applicability of the Adverse Outcome Pathway (AOP) framework to FBR in order to integrate evidence and methods into a structured mechanistic context and facilitate the application of in vitro tests in preclinical risk assessment of FBR. A targeted literature review was conducted to identify and organize biological mechanisms into a putative AOP, map available new approach methodologies, and highlight critical knowledge gaps and uncertainties. This initial framework may guide early screening for low-FBR materials and support mechanistically anchored, non-animal biocompatibility assessment strategies for medical devices.